The Role of Sharia Tourism Business Towards Economic Growth in Indonesia and Nigeria - Trimulato; Sagir Muhammad Sulaiman; Muhlis; St Hafsah Umar (Rumah Jurnal STAIN Majene, 2023)
The increasingly significant development of global tourism indirectly also has a positive impact on developing countries such as Indonesia and Nigeria. The purpose of this research is to demonstrate the development of sharia tourism in halal business, and its role in supporting the sustainable development goals (SDGs) program in Indonesia and Nigeria. The method used in this research was qualitative. Data collection techniques used by the literature from various sources. The analysis technique used is descriptive qualitative, outlining the development and potential for developing sharia tourism in Indonesia and Nigeria. Then outlines the role of its tourism in supporting the SGDs program. The results show that the sharia tourism sector has a role to support SDGs, based on its characteristics and the halal process involves many parties, so it has an impact on many parties, involving transportation service providers, ticket sales/travel agents, lodging and hotels, culinary, souvenirs and handicrafts, so move many economic actors. Sharia tourism supports SDGs, and welfare reduces poverty, food security, and economic growth provides employment, provides infrastructure, provides justice, and can build partnerships globally. In addition, Indonesia seems to be more productive than Nigeria in leading sharia tourism. Thus, the tourism sector plays an important role in the world economy because it is considered one of the contributors to economic growth in Indonesia and Nigeria.